ANALYSIS OF PRODUCTIVE WAQF FINANCIAL MANAGEMENT AT THE INDONESIAN WAKAF BOARD (BWI) REPRESENTATIVE OF RIAU PROVINCE - Andrini, Rozi (Jurnal Al-Iqtishad, 2023)
The Indonesian Waqf Agency (BWI) Representative for Riau Province exists as an independent institution to support the development of waqf in Riau Province. As an independent institution, BWI functions, one of which is to manage and develop waqf assets on a national and international scale. However, phenomena in the field show that waqf funds at BWI are still relatively small to be managed. This study aims to analyze productive waqf financial management at BWI Riau Province Representative. This research is field research (field research) with a qualitative approach. The results of the study show that the Indonesian Waqf Agency (BWI) Representative of Riau Province has carried out financial management well and at this time productive waqf financial management has been carried out according to the standards set by BWI. However, there are drawbacks, namely that it is only limited to managing the types of cash waqf deposited in Islamic banks. In addition, BWI has problems in financial management, namely the absence of a Sharia Guarantee Institution. This research is expected to provide recommendations for the BWI Riau Province Representative in managing productive waqf finances as well as material for evaluating the functions of BWI.